Analysis of Determining the Cost of Goods Production Using the Full Costing Method as a Basis for Determining the Selling Price of Rubber Rubber at PT. Sinar Belantara Indah - Sinaga, Selvi Oktaviana (First Ciera Publisher, 2024)
Production costs are very necessary in determining the cost of production of a product. The costs incurred to produce the product must be clear, so that the determination of the cost of production will be correct too. PT. Sinar Belantara Indah in determining the cost of production uses the full costing method. The full costing method is a determination of the cost of production that takes into account all elements of production costs consisting of raw material costs, labor costs and factory overhead costs. This research is a type of descriptive research, namely research conducted to determine the calculation of the cost of production in order to determine the selling price. The data used is primary and secondary data which is carried out using the accounting cycle, which starts with recording each transaction in a journal and ends with preparing the cost of production report and financial reports. In reporting the cost of production, the company classifies production costs according to the relationship between the costs and the thing being financed. The research results show that the calculation of the cost of production is the basis for determining the selling price of PT. Sinar Belantara Indah rubber latex.